Pengaruh Corporate Governance pada hubungan Corporate Social Responsibility dan nilai perusahaan. - Doni Krisna Wijaya (AKT 13 UMY 206, 2013)
This purpose of this research test the influence of a corporate governance in context corporate social responsibility and firm value. The corporate responsibility has to be based on triple bottom lines those are social, environmental, and financial. The corporate governance is represented with managerial ownership, institutional ownership, independent commissary proportion, and the member of audit committee as the moderating variable.